2010
DOI: 10.1111/j.1365-313x.2010.04305.x
|View full text |Cite
|
Sign up to set email alerts
|

A bimodular oxidoreductase mediates the specific reduction of phylloquinone (vitamin K1) in chloroplasts

Abstract: SUMMARYPlants and certain species of cyanobacteria are the only organisms capable of synthesizing phylloquinone (vitamin K 1 for vertebrates), which they use as an electron carrier during photosynthesis. Recent studies, however, have identified a plastidial pool of non-photoactive phylloquinone that could be involved in additional cellular functions. Here, we characterized an Arabidopsis bimodular enzyme -the At4g35760 gene product -comprising an integral domain homologous to the catalytic subunit of mammalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 36 publications
2
47
1
Order By: Relevance
“…Previous studies with mycobacterial and cyanobacterial VKOR-like proteins have demonstrated that the thioredoxin-like domain carries DsbAlike activity, while the VKOR-like central domain is functionally equivalent to DsbB (Singh et al, 2008;Dutton et al, 2010;Wang et al, 2011). In vitro assays show that the Arabidopsis LTO1 thioredoxin-like domain can transfer electrons to its VKOR-like central domain (Furt et al, 2010). This supports the view that the plastid protein operates in a manner similar to bacterial VKORlike proteins in regard to thiol-disulfide chemistry.…”
Section: Discussion the Plastid Vkor-like Protein Defines A Trans-thysupporting
confidence: 71%
See 4 more Smart Citations
“…Previous studies with mycobacterial and cyanobacterial VKOR-like proteins have demonstrated that the thioredoxin-like domain carries DsbAlike activity, while the VKOR-like central domain is functionally equivalent to DsbB (Singh et al, 2008;Dutton et al, 2010;Wang et al, 2011). In vitro assays show that the Arabidopsis LTO1 thioredoxin-like domain can transfer electrons to its VKOR-like central domain (Furt et al, 2010). This supports the view that the plastid protein operates in a manner similar to bacterial VKORlike proteins in regard to thiol-disulfide chemistry.…”
Section: Discussion the Plastid Vkor-like Protein Defines A Trans-thysupporting
confidence: 71%
“…In vitro enzymatic assays indicate that the Arabidopsis VKOR-like protein is active in reducing phylloquinone but not PQ, two quinones found in plastids (Furt et al, 2010). The role of phylloquinone as a structural cofactor tightly bound to PSI is well documented (Brettel, 1997).…”
Section: Discussion the Plastid Vkor-like Protein Defines A Trans-thymentioning
confidence: 99%
See 3 more Smart Citations